COMPARATIVE EFFICACY OF MODERN METHODS OF SCATOSCOPIC DIAGNOSTICS FOR NEMATODOSES OF GEESE DIGESTIVE CANAL - Mykhailiutenko, S.; Zamaziy, A. (Scientific Progress & Innovations, 2021)
Diagnostics of parasitic diseases in animal husbandry is an extremely important component of a complex of anti-epizootic measures aimed at achieving veterinary well-being and creating highly productive herds of animals. Today, both in Ukraine and in the whole world, scientists have developed and implemented in the practice of veterinary medicine a large number of methods of lifetime scatoscopic diagnostics. According to their characteristics, they are divided into qualitative and quantitative. The latter are more convenient, be-cause they allow to specifically establish the rate of the body infestation with a pathogen of a parasitic dis-ease. Therefore, the aim of the conducted research was to characterize the diagnostic efficacy of some mod-ern methods of scatoscopic diagnosing heterakosis and amidostomosis of geese. The work was performed in the Laboratory of the Department of Parasitology and Veterinary Sanitary Expert Examination of Poltava State Agrarian Academy. During the experiment, modern methods of scatoscopic diagnostics, patented in Ukraine, were compared. In particular, the methods of Sorokova (Ukrainian patent for utility model № 141225), Manoilo (Ukrainian patent for utility model № 108380), Natiahla (Ukrainian patent for utility model № 111568) for heterakosic and amidostomosic invasions of geese were tested. The studies have estab-lished a high diagnostic effectiveness of the method of Sorokova (2020), according to which a combined so-lution of lime saltpeter (Ca(NO3)2) and ammonium nitrate (NH4NO3) was used as a flotation fluid. In par-ticular, the method proved to be more effective in terms of the number of positive samples for amidostomosis and heterakosis of geese. The used technique exceeded the indicators of diagnostic efficacy of Manoilo’s methods (by 26.67 and 35.71 %, respectively) and Natiahla’s method (by 6.67 and 21.43 %, respectively). Sorokova’s method turned out to be more effective as to the number of detected eggs in the sample. In case of heterakosic invasion, as compared with the methods of Natiahla and Manoilo, it was by 13.98 and 27.56 % (p<0.05), respectively, more effective. In the case of amidostomosic invasion, Sorokova’s method was more effective in comparison with the methods of Natiahla and Manoilo by 10.69 and 30.42 % (p<0.01). Thus, the obtained data expand the choice of quantitative scatoscopic diagnostic methods for doctors of veterinary medicine while conducting diagnostic activities on goose farms.